Effects of Integrated Use of Fertilizers and Manure on Yield and Nutrient Uptake of T.Aus Rice and Mungbean in the Wheat-T.Aus Rice/Mungbean-T.Aman Rice Cropping Pattern (Bangladesh Journal of Agricultural Research, 2012)
An experiment was carried out at the Bangladesh Agricultural University (BAU) Farm, Mymensingh from rabi season of 1999 to kharif-II season of 2002 in the Old Brahmaputra Floodplain Soils (AEZ 9, Aeric Haplaquept) of Bangladesh to investigate the effect of integrated use of organic and inorganic fertilizers on yield and nutrient uptake of T.Aus rice and mungbean in the Wheat-T.  Aus/Mungbean-T.Aman cropping pattern. There were four treatments for wheat- T1: Control, T2: NPKSZnB (MYG), T3: NPKSZnB (HYG) and T4: NPKSZnB (MYG) + CD. The nutrient rates for four treatments of wheat were N0P0K0S0Zn0B0 kg/ha for T1, N80P20K50S10Zn1B1 kg/ha for T2, N120P30K75S15Zn2B2 kg/ha for T3 and N80P20K50S10Zn1B1 kg/ha + CD (5 t/ha) for T4. In T. Aus/Mungbean one-third plot of each treatment was cultivated by T. Aus rice and the rest two-thirds plot by mungbean. The rates of N, P, K, and S for  T. Aus rice were, respectively, 60, 12, 32 and 5 kg/ha for MYG, and 90, 18, 48 and 7.5 kg/ha for HYG. The corresponding rates of P, K, and S for mungbean were 10, 13, and 5 kg/ha for average yield goal (AYG). The results showed that grain (3.46 t/ha) and straw yields (5.19 t/ha) of T. Aus rice increased significantly due to application of fertilizers. The highest mean seed yield of 0.56 t/ha and stover yield of 1.99 t/ha in mungbean were obtained from PKS plus inoculum plus residual NPKSZnB for HYG treatment. The N, P, K, S, Zn, and B uptake by T.Aus/Mungbean remarkably increased with increasing supply of nutrients. The highest uptake of N, P, K, S, Zn, and B by the crops was noted in the treatment T3  that received HYG fertilizers in T. Aus rice. The removal of N ranged from 27.3 to 63.2 kg/ha and 29.8 to 48.1 kg/ha, P from 5.62 to 15.80 kg/ha and 2.60 to 4.69 kg/ha, K from 35.8 to 71.8 kg/ha and 21.9 to 37.4 kg/ha, S from 4.08 to 10.26 kg/ha and 2.12 to 4.11 kg/ha, Zn from 44 to 132 g/ha and 56 to 101 g/ha, B from 17 to 70 g/ha and 7 to 16 g/ha by T.Aus rice and mungbean, respectively.  Application of cowdung along with chemical fertilizers resulted in markedly higher uptake of nutrients. The application of NPKS (HYG) fertilizers remarkably increased the crop yield. The lowest grain yield and the lowest nutrient uptake were noted in control plots receiving no fertilizer or manure.DOI: http://dx.doi.org/10.3329/bjar.v36i4.11760Bangladesh J. Agril. Res. 36(4): 685-695, December 2011